"We're Still Here": Memory and Commemoration in the Alliances between the American Indian Movement and Welsh Nationalists. (2nd April 2020) - Rennard, Kate
ABSTRACT: Focusing on the role of historical memory and commemoration, this article explores the exchange of ideology and strategy between the American Indian Movement (AIM) and Welsh nationalists in the late twentieth-century. While these links might seem unexpected, they are part of a larger story of connections between the two groups, in which they shared information and supported each other's campaigns. Despite the differences between the movements involved, these activists bonded through shared experiences of colonialism; their histories, in particular, were not being remembered. This article  argues for a re-evaluation of AIM's legacy through the transnational effects of their protests involving remembrance. AIM's use of counter-commemorations not only shaped the tactics of historical remembering used by some Welsh nationalist groups but these Welsh activists, in turn, used the historical memory of AIM to raise awareness of their own causes. This article, therefore, uncovers some of the complicated and diverse ways that the American Indian Movement has influenced Welsh nationalism.